Kajian Ontologi, Epistimologi, dan Aksiologi dalam Penerapan Filsafat Stoikisme Mengatasi Stress Pada Remaja - Neisha, Fella Hanna; Karneli, Yeni; Solfema, Solfema (Program Studi Bimbingan dan Konseling, 2024)
This study explores the integration of Stoic philosophy into guidance and counseling practices, specifically focusing on its application in managing stress among adolescents. It examines the philosophical underpinnings of guidance and counseling through the lenses of ontology, epistemology, and axiology, highlighting their interconnectedness in shaping the practice. The research utilizes a qualitative descriptive approach, employing a literature review methodology to analyze relevant scholarly works and texts. The study reveals that Stoic philosophy, with its emphasis on self-control, acceptance, and focusing on what is within one's control, offers a valuable framework for addressing stress. The core principles of Stoicism, particularly the